Quantum Mechanical Calculations for Reaction Path of O-R Bond Breakage in Some of Cefpodoxime Prodrugs - Kubba, R.M. (Asian Journal of Chemistry, 2018)
This work is Unrestricted Hartree Fock (UHF) quantum mechanical calculations of proton transfer and reaction path of (O-R) bond rupture energies in nine cefpodoxime prodrug derivatives of different substituted organic groups, at their optimize geometries. The calculation included geometrical structure, some of physical properties such as standard heat of formation, dipole moment and total energies, using Gaussian-09 program. Comparison was done between the total energies of the reactants, activation energies, transition states and end products. All the calculations are reported in the vacuum phase. The results showed that some of the substituted organic groups can be used as carrier linkages for the acidic cefpodoxime drug.